The Implementation of School-Based Management in Islamic Elementary Schools - Ika Yatri; Arum Fatayan; Hanni Funica Granatuma (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims at determining to what extent the implementation of school-based management in Islamic elementary schools. The method applied in this study was descriptive qualitative, emphasizing the analysis of sentences, arguments, or data collected directly in the field. The approach taken by researchers was a case study. It is a series of scientific activities that are carried out regularly, structured, and comprehensively on a program, activity, or event at the individual, group, or organizational level to gain an in-depth understanding of what is being. Data in this study was collected using the triangulation technique (observation, interviews, and documentation). The results indicated that the principles of the policies imposed by the Islamic elementary schools are curriculum and teaching development, selection of teachers and teaching staff, student management, support for facilities and infrastructure, adequate financing, parent-school relations, and the realization of comfortable school culture environment. The implementation of school-based management in Islamic elementary schools proves the improvement in quality and brilliant achievements of educational sectors at national and international levels.